2017
DOI: 10.1016/j.rbre.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids, inflammatory status and biochemical markers of patients with systemic lupus erythematosus: a pilot study

Abstract: Supplementation with omega-3 had no impact on serum concentrations of IL-6, IL-10, leptin and adiponectin in women with SLE and low disease activity. There was a significant decrease of CRP levels as well as evidence that omega-3 may impact total and LDL-cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In line with our study, Agh et al (2017) showed that omega-3 fatty acids supplementation (720 mg of EPA + 480 mg of DHA) for 8 weeks decreased serum FIGURE 1 Summary of patient flow diagram hs-CRP levels in patients with CAD (Agh et al, 2017). In another study, omega-3 fatty acids supplementation (1,080 mg of EPA + 200 mg of DHA) for 12 weeks was effective for reducing CRP levels in women with systemic lupus erythematosus and low disease activity, though had no impact on circulating interleukin 6, interleukin 10, leptin, and adiponectin (Borges et al, 2016). Our previous study documented that omega-3 fatty acids supplementation from flaxseed oil at a dosage of 2 g/day for 12 weeks significantly decreased serum hs-CRP, while increased plasma TAC and GSH in diabetic patients with foot ulcer (Soleimani, Hashemdokht, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study, Agh et al (2017) showed that omega-3 fatty acids supplementation (720 mg of EPA + 480 mg of DHA) for 8 weeks decreased serum FIGURE 1 Summary of patient flow diagram hs-CRP levels in patients with CAD (Agh et al, 2017). In another study, omega-3 fatty acids supplementation (1,080 mg of EPA + 200 mg of DHA) for 12 weeks was effective for reducing CRP levels in women with systemic lupus erythematosus and low disease activity, though had no impact on circulating interleukin 6, interleukin 10, leptin, and adiponectin (Borges et al, 2016). Our previous study documented that omega-3 fatty acids supplementation from flaxseed oil at a dosage of 2 g/day for 12 weeks significantly decreased serum hs-CRP, while increased plasma TAC and GSH in diabetic patients with foot ulcer (Soleimani, Hashemdokht, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews on this subject (5,92) reveal that approximately half of the clinical trials performed employing ω-3 supplementation in lupus patients report a reduction in disease activity (11-13, 16, 18, 93). Many studies that did not observe a reduction in disease activity reported improvements in other areas, such as a reduction in serum triglycerides (9,10) or biomarkers of inflammation and oxidative stress (9,15). A critical impediment to evaluating the efficacy of ω-3 supplementation in these trials is the inconsistency in measuring and reporting the ω-3 levels in subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, low ω-3 HUFA intake is associated with exacerbated disease activity, adverse serum lipids, and atherosclerotic plaques in lupus patients (7), and a recent study by the Michigan Lupus Epidemiology and Surveillance (MiLES) program reported that positive patient-reported outcomes were associated with high consumption of ω-3 fatty acids and low dietary ω-6:ω-3 ratios (8). Most intervention trials implementing ω-3 HUFA supplementation in lupus patients report lessening of symptoms (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, there is variability across studies with some trials failing to show positive results.…”
Section: Introductionmentioning
confidence: 99%
“…However, subclinical inflammation assessed by variations of serum CRP levels in predominantly ‘normal’ ranges have previously been linked to relevant clinical parameters such as disease activity and surrogate markers for atherosclerosis in SLE patients. 17,19 Previous interventional studies which administered omega-3 PUFA containing fish oil to SLE patients produced conflicting results in this regard: amelioration of systemic inflammatory markers was seen in some 20,21 but not all studies. 22,23 Of note, individual nutrition status omega-3 PUFA content in the blood cells was not assessed in these studies.…”
Section: Discussionmentioning
confidence: 99%